Editorial Opinion - AKYEŞİLMEN, Nezir (Cyberpolitik Journal, 2023)
Dear Readers, We are proud to present to you the fourteenth issue of the Cyberpolitik Journal. It is a great honor for all of us to continue the journey that we started seven years ago without interruption. As the digital world grows every day and every second, new development and new technologies emerge, and we are trying to read and understand this area within our limitations. This issue has a new research and in-depth analysis.